Partial Versus Radical Nephrectomy in Patients with Renal Cell Carcinoma: A Systematic Review and Meta-analysis - Yang, Yong (Urology Journal, 2020)
Purpose: Radical nephrectomy (RN) and partial nephrectomy (PN) are widely used for early-stage renal cell carcinoma (RCC). However, the results were inconsistent while comparing the efficiency of RN and PN. This study aimed to assess the perioperative effectiveness of RN and PN for treating RCC. Material and Methods: PubMed, Embase, and the Cochrane Library electronic database were searched for studies on adults with RCC comparing RN and PN published until September 2019. The perioperative efficacy and safety outcomes were calculated using odds ratio (OR) and standard mean difference (SMD) with 95% confidence intervals (CIs) for dichotomous and continuous data, respectively. Subgroup analysis were conducted based on tumor stage and surgery methods for evaluation of the treatment effect on specific subsets. Results: A total of 23 studies involving 30,018 patients with RCC were included in this meta-analysis. Notably, RCC treated with PN was associated with low incidences of hospital mortality (OR: 0.58; 95% CI: 0.38–0.89; P = 0.013) and reoperation rate (OR: 0.74; 95% CI: 0.58–0.95; P = 0.016) as compared to RN. However, PN was associated with an increased risk of overall postoperative complications (OR: 1.40; 95% CI: 1.17–1.68, P < 0.001), postoperative hemorrhagic complications (OR: 1.92; 95% CI: 1.28–2.87, P = 0.002), and urinary fistula (OR: 17.65; 95% CI: 5.35–58.30, P < 0.001) as compared to RN. Conclusion: These findings suggested that PN was associated with lower incidences of hospital mortality and reoperation rate, whereas RN was associated with fewer complications.